Structural Characterization and Anti-Nonalcoholic Fatty Liver Effect of High-Sulfated Ulva pertusa Polysaccharide - Yuzhou Wan; Lin Liu; Bo Zhang; Shaopeng Wang; Xiaoqian Wang; Kexu Chen; Yuxi Li; Tingting Zhao; Huimin Qi (MDPI AG, 2022)
The high-sulfated derivative of Ulva pertusa polysaccharide (HU), with unclear structure, has better anti-hyperlipidmia activity than U pertusa polysaccharide ulvan (U). In this study, we explore the main structure of HU and its therapeutic effect against nonalcoholic fatty liver disease (NAFLD). The main structure of HU was elucidated using FT-IR and NMR (13C, 1H, COSY, HSQC, HMBC). The anti-NAFLD activity of HU was explored using the high-fat diet mouse model to detect indicators of blood lipid and liver function and observe the pathologic changes in epididymal fat and the liver. Results showed that HU had these main structural fragments: →4)-β-D-Glcp(1→4)-α-L-Rhap2,3S(1→; →4)-α-L-Rhap3S(1→4)-β-D-Xylp2,3S(1→; →4)-α-L-Rhap3S(1→4)-β-D-Xylp(1→; →4)-α-L-IdopA3S(1→4)-α-L-Rhap3S(1→; →4)-β-D-GlcpA(1→3)-α-L-Rhap(1→; →4)-α-L-IdopA3S(1→4)-β-D-Glcp3Me(1→; →4)-β-D-Xylp2,3S(1→4)-α-L-IdopA3S(1→; and →4)-β-D-Xylp(1→4)-α-L-IdopA3S(1→. Treatment results indicated that HU markedly decreased levels of TC, LDL-C, TG, and AST. Furthermore, lipid droplets in the liver were reduced, and the abnormal enlargement of epididymal fat cells was suppressed. Thus, HU appears to have a protective effect on the development of NAFLD.